Cell competition corrects noisy Wnt morphogen gradients to achieve robust patterning in the zebrafish embryo - Yuki Akieda (Nature Portfolio, 2019)
Gradients of morphogens such as Wnt provide instructive cues for cell identities during development. Here, the authors report that in the developing zebrafish embryo, cell competition and elimination of unfit cells are required for proper Wnt gradient formation.